Factors associated with the quality of corneas retrieved for transplantation by Eye Banks: a scoping review protocol - Felipe Machado Mota; Marcos Antonio Ferreira Júnior; Gustavo Moura Maidana; Andréia Insabralde de Queiroz Cardoso; Bruna Dias Abes; Mayra Dias; Letícia Lima Meza (BMJ Open)
Introduction The cornea is an avascular and transparent layer of connective tissue crucial to retinal image quality. Diseases can impair its quality, affecting vision. Keratoplasty is the only therapy capable of restoring vision quality in severe corneal involvement. Despite the established practice of transplantation, access to corneal tissue is limited in many places, and the quality of retrieved corneas is not always adequate, resulting in disqualification. Not all factors affecting tissue quality are fully understood due to the multifactorial nature of processes and variations in procedures globally.Objective The objective is to map the global literature to establish the factors associated with the clinical and sociodemographic conditions of donors, and the conditions inherent in the processing of corneas that can influence the quality of this tissue for transplantation purposes.Methods and analysis A scoping review will be developed based on the methodological framework of the Joanna Briggs Institute. The scientific report will follow the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension checklist for Scoping Reviews. Searches will be conducted in 30 indexed and 12 grey literature databases, without time or location restrictions. The selection of studies will be carried out in three distinct phases: screening, eligibility and inclusion. After defining the sample, data from the selected studies will be systematically extracted into an electronic spreadsheet. The results will be presented descriptively through tables and graphs of absolute and relative frequency. In addition, the PRISMA Scoping Review flow chart will be presented to present the process of searching, including and excluding articles and documents.Ethics and dissemination This scoping review study does not require prior ethical approval as it uses publicly available and already published studies. The research protocol is registered in the Open Science Framework (osf.io/bw6r7). The findings will be submitted for publication in peer-reviewed scientific journals and presented at ophthalmology and/or transplantation conferences through oral presentations or posters.